The Competency Development of Fishery Product Market Analyst at the Directorate General of Product Competitiveness, Ministry of Marine Affairs and Fisheries Republic of Indonesia - Zeni Aniroh; Firman Hadi Rivai; R.N. Afsdy Saksono (International Journal of Economics Development Research (IJEDR), 2025)
This study aimed to analyze the factors that influence the competency development of Fishery Product Market Analysts (APHP) and formulate a competency development model appropriate for the competency development of APHP at the Directorate General of Product Competitiveness, Ministry of Marine Affairs and Fisheries. This study was conducted using a qualitative approach and case study method. The data collection techniques used were interviews and document reviews. The study’s results indicate that several factors influence the suboptimal competency development of APHP. First, the Human Capital Development Plan (HCDP) for employees within the Directorate General of Product Competitiveness, including the APHP, has not been completed. Second, the commitment of the APHP team to prepare APHP training learning tools is not yet strong, mainly due to their busy schedules. Third, the coordination function is not yet strong, assuming that implementing competency development is only the responsibility of the Civil Service Training Center (Balai Diklat Aparatur). Based on the study’s results, the author formulated and recommended an APHP competency development model at the Directorate General of Product Competitiveness.